PENGAPLIKASIAN LIMBAH POTONGAN KAIN RAJUT HASIL SISA PRODUKSI KAMPOENG RADJOET BINONG JATI - Shidiq, Hafiid; Sadika, Fajar; Muchlis, Muchlis (eProceedings of Art & Design, 2024)
Kampung Radjoet is a knitting industry in Bandung. Kampoeng Radjoet produces various types of knitted products ranging from sweaters, vests, cardigans, etc. However, the massive production in Radjoet Village produces production waste such as pieces of knitted fabric that can disturb the environment. Therefore, Kampung Radjoet wants to utilize the potential of fabric scraps waste from the remaining knitted production to produce new wearable products. Through an observational approach, this research aims to understand the phenomenon of leftover knitted fabric waste by conducting a field survey at Kampoeng Radjoet. In addition, it uses simple processing techniques and exploratory methods to find the potential of the waste. The final result is an exploration of the leftover knit fabric waste that can be used as recommendations for new product innovations for Kampoeng Radjoet from more valuable knit fabric waste. Keywords : Kampoeng Radjoet, exploration, waste knit fabric scraps from leftover production.